Surveillance of Escherichia coli in a fish farm of Sylhet, Bangladesh (Bangladesh Journal of Zoology, 2021)
The study was accomplished to investigate Escherichia coli from two freshwater fish, Tilapia (Oreochromis niloticus) and Mrigal (Cirrhinus mrigala), collected from a fish farm in Sylhet, Bangladesh. Six of each fish were analyzed to isolate and detect Escherichia coli, and E. coli was identified based on morphological and biochemical characteristics. The antibiogram of E. coli was investigated in different generations using eight antibiotic discs such as Chloramphenicol (CH), Streptomycin (S), Gentamycin (G), Ciprofloxacin (CI), Co-trimethoxazole (CO), Azithromycin (AZI), Erythromycin (E) and Novobiocin (NV), and the sensitivity of E. coli was found as 100%, 25%, 100%, 75%, 87.5%, 81.25%, 0%, 0% respectively. Among the 8 antibiotics, for Erythromycin (E) and Novobiocin (NV), the observed resistance pattern of E. coli was 81.25% and 87.5% respectively, whereas, for the rest of the antibiotics, it was 0%.Bangladesh J. Zool. 48(2): 335-346, 2020